Adverse motor outcome after paediatric ischaemic stroke: A nationwide cohort study. Issue 3 (16th February 2022) - Svensson, Katarina; Walås, Anna; Bolk, Jenny; Bang, Peter; Sundelin, Heléne E. K.
Abstract: Background: Various frequencies of adverse motor outcomes (cerebral palsy and hemiplegia) after paediatric ischaemic stroke have been reported. Few reports on the risks of adverse motor outcomes in nationwide cohorts and contributing risk factors are available. Objectives: To assess risk of adverse motor outcome and potential risk factors thereof after paediatric ischaemic stroke in a nationwide cohort. Methods: This nationwide matched cohort study identified 877 children <18 years of age diagnosed with ischaemic stroke through the Swedish national health registers from 1997 to 2016. These children, exposed to ischaemic stroke, alive 1 week after stroke, were matched for age, sex and county of residence with 10 unexposed children. Using Cox regression, we estimated the risk of adverse motor outcomes in children with stroke compared to that in unexposed children. Logistic regression was applied to compare the characteristics of children with and without adverse motor outcomes after stroke. Results: Out of the 877 children with ischaemic stroke, 280 (31.9%) suffered adverse motor outcomes compared with 21 (0.2%) of the 8770 unexposed: adjusted hazard ratio (aHR) 167.78 (95% confidence interval (CI) 107.58, 261.66). There were no differences between risk estimates of adverse motor outcome according to age at stroke: perinatal stroke (aHR 124.11, 95% CI 30.45, 505.84) and childhood stroke (aHR 182.37, 95% CI 113.65, 292.64). An association between adverse motor outcome and childhood stroke aOR 1.56 (95% CI 1.05, 2.31) was found when analysing only children with ischaemic stroke. No associations were found between adverse motor outcome and sex, gestational age or parental age at birth. Conclusions: The risk of adverse motor outcome is substantial after paediatric ischaemic stroke, especially childhood stroke, confirming results of previous smaller studies. This study found no associations between sex, gestational age or parental age and adverse motor outcome after paediatric ischaemic stroke.